Programmed Cell Death-Dependent Host Defense in Ocular Herpes Simplex Virus Infection - Guo, Hongyan; Koehler, Heather S.; Dix, Richard D.; Mocarski, Edward S. (Frontiers in Microbiology, 2022)
Herpes simplex virus type 1 (HSV1) remains one of the most ubiquitous human pathogens on earth. Recurrent oral infection typically manifests as the common cold sore. However, HSV1 also is responsible for a range of ocular diseases in immunocompetent persons that are of medical importance, causing vision loss that may result in blindness. These include a recurrent corneal disease, herpes stromal keratitis, and a retinal disease, acute retinal necrosis, for which clinically relevant animal models exist. Diverse host immune mechanisms mediate control over herpesviruses, sustaining lifelong latency in neurons. Antiviral immunity may also contribute to disease pathogenesis. Herpesviruses, including HSV1, have evolved cell death evasion strategies to subvert clearance of infection and modulate inflammation. In this review, we discuss the key studies that have contributed to our current knowledge of cell death pathways including apoptosis, necroptosis, and pyroptosis manipulated by HSV1 and relate the contributions of cell death to infection and potential ocular disease outcomes.